PENGARUH GENDER DAN PENGALAMAN AUDIT TERHADAP AUDIT JUDGMENT DI KANTOR AKUNTAN PUBLIK (KAP) JAKARTA SELATAN - Kerin Cahya Febrianty; Mulia Rahmah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
This study examines the effect of gender and audit experience on audit judgment at KAP South Jakarta. Respondents in this study were auditors who worked in the South Jakarta area. The number of auditors who became the sample of this study were 50 respondents from 10 KAP in South Jakarta. The sampling method used in this research is purposive sampling, while the data processing method used is multiple regression analysis. The result of this study indicate that gender and audit experience partially or simultaneously affect audit judgment at South Jakarta KAP.